Unraveling the Therapeutic Potential of Andrographis paniculata for Tuberculosis: Molecular Docking Study - Farid, Muhammad; Al Madury, Shalahuddin; Muslim, Ahmad Suriyadi; ‘Aini, Zakiyyah Qurrotul (Jurnal Kimia Riset, 2025)
Tuberculosis (TB) remains a global health challenge with increasing drug resistance. This study aims to explore the potential of Andrographis paniculata as an alternative anti-TB therapy through an in silico approach. The study was conducted using the molecular docking method using Biovia Discovery Studio, AutoDock 1.5.7, and ChemDraw 3D software. The target proteins analyzed were 1TYP and 3R6C. which play a role in the biosynthesis of Mycobacterium tuberculosis cell walls. The docking results showed that dehydroandrographolide and neoandrographolide compounds have lower binding energies than ethambutol, with ΔG values of -9.54 kcal/mol and -9.04 kcal/mol at 3R6C, respectively. Stable hydrogen and non-hydrogen interactions indicate a stronger inhibitory potential against protein targets. Pharmacokinetic analysis through SwissADME and PKCMS confirmed that this compound meets Lipinski's Rule of 5 criteria, and has lower toxicity compared to conventional TB drugs. Thus, this study provides new insights into the development of natural compound-based TB therapy, which is potentially more effective and has minimal side effects. Further studies are needed to confirm the activity of this compound through in vitro and in vivo tests.